Ozone Loss From Quasi-Conservative Coordinate Mapping During the 1999-2000 SOLVE Campaign - Richard, E.; Schoeberl, M. R.; Braathen, G. O.; Newman, P. A.; Goutail, F.; McGee, T.; Bhartia, P. K.; Burris, J.; Bojkov, B. R.; Lait, L. R.; Browell, E. V. (2001)
During the winter of 1999-2000, the Sage III Ozone Loss and Validation Experiment (SOLVE) field experiment took place in Kiruna, Sweden. The purpose of SOLVE was to examine ozone depletion mechanisms in the Arctic stratosphere (from about 10 to 50 km altitude) during the winter and early spring, when a band of strong winds (the 'polar vortex') circle the pole. Measurements of stratospheric ozone were made by several different kinds of instruments in different meteorological situations. We analyzed these data using the 'quasi-conservative coordinate mapping' technique, in which the measurements are analyzed in terms of meteorological properties ('potential temperature' and 'potential vorticity') which tend not to change very much over a few days. This technique reduces or removes the changes that are associated with the polar vortex moving around. Over longer time periods, potential temperature and potential vorticity change as air cools and descends within the polar vortex. We account for these changes by calculating the trajectories of air parcels, and this enables us to extend the analysis over a ten-week period from January 10 to March 17, 2000. Using data from the NASA ER-2 aircraft, from the DIAL and AROTEL laser sounders on the NASA DC-8 aircraft, and balloon-borne ozonesondes, our analysis reveals changes in ozone which, because we have removed the effects of polar vortex motion and the descending air, indicate chemical destruction of ozone in early 2000. We find a peak decline rate of approximately 0.03 ppmv/day near 470 K of potential temperature (near 20 km) in mid-January which sinks in altitude to around 440 K (near 18 km) in mid-March.